Clarifying the ambiguity surrounding Organizational Citizenship Behavior (OCB) and related behavioral constructs - Bambale, Abdu Ja’afaru; Mohd Shamsudin, Faridahwati; Subramaniam, Chandrakantan (2012)
This paper is an attempt to provide a medium for contributing to OCB knowledge base.Though essentially literature based, however, it tries to clarify ambiguity and confusion surrounding the conceptual underpinnings and thus understanding of OCB and related constructs.Most researchers and readers find difficulty to differentiate OCB from prosocial citizenship behavior, extra-role behavior, spontaneous behavior and contextual behavior resulting to the use of the constructs interchangeably, thus leading to errors in measurement.OCB is such an important construct to organizations as it has been found to improve their effective functioning and goal attainment by lubricating and enhancing social networks. Because of the ongoing importance of OCB to organizations, employees, management and the marketplace efforts should be made to encourage more research around the construct and other related constructs.